87.5k views
4 votes
10-(3x-1)/2=(6x+3)/11
If someone could help that would be great thank you!

1 Answer

6 votes

If it is :


10 - ( (3x - 1))/(2) = ((6x + 3))/(11) \\

Multiply both sides by 22


(22 * 10) - 11 * (3x - 1) = 2 * (6x + 3) \\


220 - 33x + 11 = 12x + 6


- 33x + 231 = 12x + 6

Plus both sides 33x


231 = 33x + 12x + 6


231 = 45x + 6

Subtract sides minus 6


231 - 6 = 45x


45x = 225

Divided sides by 45


x = (225)/(45) \\


x = 5

_________________________________

If it is :


(10 - (3x - 1))/(2) = (6x + 3)/(11) \\

Multiply sides by 22


(11 * 10) - 11 * (3x - 1) = 2 * (6x + 3) \\


110 - 33x + 11 = 12x + 6


- 33x + 121 = 12x + 6

Plus sides 33x


121 = 12x + 33x + 6


121 = 45x + 6

Subtract sides minus 6


121 - 6 = 45x


45x = 115


x = (115)/(45) \\


x = (23)/(9) \\

_________________________________

And we're done.

Thanks for watching buddy good luck.

♥️♥️♥️♥️♥️

User Scotchi
by
5.0k points